2022
DOI: 10.1039/d1ta09847k
|View full text |Cite
|
Sign up to set email alerts
|

In silico design of dual-doped nitrogenated graphene (C2N) employed in electrocatalytic reduction of carbon monoxide to ethylene

Abstract: The electrocatalytic reduction of carbon monoxide (CO) to valuable multi-carbon chemicals is among the most promising methods to ensure a sustainable carbon cycle. Many catalysts have been developed to achieve...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 65 publications
(79 reference statements)
0
7
0
Order By: Relevance
“…The potential of B, P doped C 2 N monolayer as metal-free catalyst for reducing CO to C 2 H 4 was explored (Wang et al, 2022). It was shown that B&P/C 2 N catalysts contribute to C-C coupling and prevent catalyst poisoning due to suitable adsorption energy for CO and lower ethylene desorption energy.…”
Section: Heteronuclear Dacsmentioning
confidence: 99%
See 2 more Smart Citations
“…The potential of B, P doped C 2 N monolayer as metal-free catalyst for reducing CO to C 2 H 4 was explored (Wang et al, 2022). It was shown that B&P/C 2 N catalysts contribute to C-C coupling and prevent catalyst poisoning due to suitable adsorption energy for CO and lower ethylene desorption energy.…”
Section: Heteronuclear Dacsmentioning
confidence: 99%
“…After the introduction of SeSA, the free energy of CO* decreased from 1.28 (MoSA) to 1.15 eV (MoSA-SeSA), indicating that the synergistic effect of MoSA-SeSA can significantly promote the generation of CO ( Sun et al, 2022 ). The potential of B, P doped C 2 N monolayer as metal-free catalyst for reducing CO to C 2 H 4 was explored ( Wang et al, 2022 ). It was shown that B&P/C 2 N catalysts contribute to C-C coupling and prevent catalyst poisoning due to suitable adsorption energy for CO and lower ethylene desorption energy.…”
Section: Dacsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides g‐C 3 N 4 , the nitrogen‐rich 2D carbon nitride family contains several materials, and some of them, including C 2 N, C 3 N, etc., were also studied for electrocatalytic applications in recent years. [ 148–157 ] Taking C 2 N as an example, it consists of benzene rings connected by nitrogen atoms to constitute large six‐membered aromatic rings with two nitrogen atoms facing each other, leading to the formation of periodically uniform 0.83‐nm‐sized holes. [ 155,158 ] Shinde et al.…”
Section: Emerging Graphene Analogues For Efficient Electrocatalysismentioning
confidence: 99%
“…Many studies have focused on transition-metal surfaces, metal oxides, , or metal atoms coordinated on substrate surfaces. , However, the cost, abundance, and toxicity are always issues for these precious metals. Carbon-based catalysts have an advantage in environmental friendliness, durability, high mobility, and flexible synthesis of different motifs. The modification of electronic structures is one of the straightforward strategies to improve material properties, and many have utilized B, N, or P atom doping toward sp 2 (graphene) and sp 3 (nanodiamond) carbon atoms for nonmetal catalysis. However, studies concerning the combination of sp–sp 2 hybrid systems are relatively scarce. Graphyne family members are carbon allotropes consisting of a network of sp 2 and sp hybridization.…”
Section: Introductionmentioning
confidence: 99%